POPULAR CULTURE AMONG STUDENTS AS FUJOSHI IN ENGLISH LITERATURE (Karya Ilmiah Mahasiswa (KIMA), 2022)
Popular culture is a culture that created by the people who enjoy that culture. One of the most popular cultures among certain people called Boys Love genre. The people who enjoy this genre called Fujoshi. Fujoshi are all over the world, included Indonesia. This study aimed to determine the origin of students as Fujoshi in English Literature of Universitas Muslim Indonesia discover about Boys Love genre and the factors of why they like this genre. The researcher used qualitative research and ethnography study as the research method. There are two data sources used in this study, namely primary data and secondary data. The researcher collected the primary data through in-depth interview with the informants and obtained the secondary data from literary media such as books and articles in journals, direct or indirectly obtained from website through internet media. In this research, the researcher found out the origin of the Fujoshi figured out about Boys Love genre and the factors that make them like this genre. As the result of this research, the researcher found out that two Fujoshis discover about Boys Love for the first time through website fanfiction.net, two of them through Facebook, two of them through Youtube, and one of them through WhatssApp application. As for the factors that cause Fujoshi liking Boys Love genre, there are internal factors; curiosity, bored with the monotonous romance straight genre, and dislikes female characters who are weak. For the external factors; various kinds of Boys Love contents, which Anime, Manga, Fanfiction, and Drama series. The researcher concluded that all of the Fujoshi discovered about Boys Love was through internet media.  As for the factors that cause Fujoshi liking Boys Love genre, there are internal factors, which come from the Fujoshi themselves and external factors, which come from outside.